CD47 promotes T-cell lymphoma metastasis by up-regulating AKAP13-mediated RhoA activation. (6th January 2021) - Kitai, Yuichi; Ishiura, Marie; Saitoh, Kodai; Matsumoto, Naoki; Owashi, Kimiya; Yamada, Shunsuke; Muromoto, Ryuta; Kashiwakura, Jun-ichi; Oritani, Kenji; Matsuda, Tadashi
Abstract: CD47, a 50 kDa transmembrane protein, facilitates integrin-mediated cell adhesion and inhibits cell engulfment by phagocytes. Since CD47 blocking promotes engulfment of cancer cells by macrophages, it is important to clarify the mechanism of CD47 signaling in order to develop treatments for diseases involving CD47-overexpressing cancer cells, including breast cancer and lymphoma. Here, we show that CD47 plays an essential role in T-cell lymphoma metastasis by up-regulating basal RhoA activity independent of its anti-phagocytic function. CD47 interacts with AKAP13, a RhoA-specific guanine nucleotide exchange factor (GEF), and facilitates AKAP13-mediated RhoA activation. Our study shows that CD47 has a novel function on the AKAP13-RhoA axis and suggests that CD47–AKAP13 interaction would be a novel target for T-cell lymphoma treatment. Abstract : CD47-mediated RhoA activation promotes T-cell lymphoma